2021
DOI: 10.3390/antibiotics10060711
|View full text |Cite
|
Sign up to set email alerts
|

A New Antifungal-Loaded Sol-Gel Can Prevent Candida albicans Prosthetic Joint Infection

Abstract: Fungal PJI is one of the most feared complications after arthroplasty. Although a rare finding, its high associated morbidity and mortality makes it an important object of study. The most frequent species causing fungal PJI is C. albicans. New technology to treat this type of PJI involves organic–inorganic sol-gels loaded with antifungals, as proposed in this study, in which anidulafungin is associated with organophosphates. This study aimed to evaluate the efficacy of an anidulafungin-loaded organic–inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Fungal PJIs typically present with mild symptomatology and, therefore, diagnosis may be delayed [ 12 , 17 ]. Among these cases, the indolent course of Candida PJIs may be indicative of direct contamination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal PJIs typically present with mild symptomatology and, therefore, diagnosis may be delayed [ 12 , 17 ]. Among these cases, the indolent course of Candida PJIs may be indicative of direct contamination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 16 Besides focusing on the specific clinical manifestations of PJI, clinical features such as fever, erythema, swelling, pain, and joint dysfunction, although not unique to PJI, indeed increase the likelihood of infection when present. 17 , 18 Rapid recognition of these symptoms and prompt initiation of further evaluation are critical for achieving optimal treatment outcomes in patients with periprosthetic joint infections.…”
Section: Diagnosismentioning
confidence: 99%
“…The antibiotics that have been loaded onto these coatings are vancomycin [91,96,97,101,105,110,116], aminoglycosides (mainly gentamicin [93,99,100,106,109,113] and tobramycin), tetracyclines (especially doxycycline [98,103] and tetracycline) [102], cephalexin [111], moxifloxacin [112,118], and mixtures of antibiotics such as vancomycin plus tigecycline [108]. Further studies have demonstrated that antifungals, such as fluconazole and anidulafungin, loaded in a coating are effective to prevent C. albicans infection both in vitro [114] and in vivo [115].…”
Section: Coating Loaded With Antibiotic For Titanium Alloysmentioning
confidence: 99%